Impact of Biogas Purification System on Generated Power in Gas Engine Generator - Fadlilatul Taufany; Bobby Rama Jaya R; Ardhiya Ardhiya (Institut Teknologi Sepuluh Nopember, 2015)
One of alternative renewable energy is biogas, which is the end product of anaerobic degradation by methanogens bacteria. In general, biogas contains CH4, CO2, H2S and H2O. Biogas is potential in a power generation but must be purified to meet the desired specifications by removing its impurities, i.e. CO2, H2S and H2O. This research aims to perform a feasibility study for the biogas purification with respect to CO2 and H2S removal by utilizing various alkalines and their respective salts (NaOH, KOH, Ca(OH)2, Na2CO3, K2CO3, CaCO3) as the absorbent. Additionally, its impacts on generated power are also being studied. The results indicate that NaOH was the optimum absorbent in perspective of technical and economical aspects.